2016
DOI: 10.1016/j.placenta.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

High levels of HtrA4 observed in preeclamptic circulation drastically alter endothelial gene expression and induce inflammation in human umbilical vein endothelial cells

Abstract: IntroductionPreeclampsia (PE) is a life-threatening pregnancy disorder characterized by wide-spread endothelial dysfunction. Placental factors circulating in the maternal blood are believed to cause endothelial dysfunction. Our previous study identified HtrA4 as a placenta-specific serine protease that is released into the maternal circulation and significantly increased in early-onset PE. In this study, we examined the impact of HtrA4 on expression of endothelial genes related to vessel biology, using human u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
(52 reference statements)
1
21
0
Order By: Relevance
“…Placental HtrA4 expression and its circulating levels are significantly increased in early, but not late onset, PE at the time of disease presentation in the third trimester (21, 2630). We have also demonstrated that high levels of HtrA4 detected in early onset PE inhibit tube formation and induce proinflammatory factors in endothelial cells (21, 31). These data suggest that HtrA4 may represent a placenta‐derived contributor of endothelial dysfunction in early‐onset PE development.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Placental HtrA4 expression and its circulating levels are significantly increased in early, but not late onset, PE at the time of disease presentation in the third trimester (21, 2630). We have also demonstrated that high levels of HtrA4 detected in early onset PE inhibit tube formation and induce proinflammatory factors in endothelial cells (21, 31). These data suggest that HtrA4 may represent a placenta‐derived contributor of endothelial dysfunction in early‐onset PE development.…”
mentioning
confidence: 71%
“…We have previously identified that serine protease HtrA4 is produced specifically by the placenta and significantly up‐regulated in early onset PE (21, 2630). We have further reported that high levels of circulating HtrA4 in PE may be a potential causal factor of endothelial dysfunction (21, 31). Here, we demonstrated that high levels of circulating HtrA4 could cleave the main VEGFA receptor KDR to disrupt endothelial cell function and inhibit the VEGFA‐induced angiogenesis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The mechanisms underlying PE is still unclear but generally accepted that in PE, the factors released from placenta into the maternal circulation induce inflammation [3]. Significantly elevated circulating factors in PE include cytokines and antiangiogenic factors and these factors modulate trophoblast invasion [4]. The hypothesis produced by Ahmed and Ramma suggested that preeclampsia might be result of the imbalance between new-onset inflammatory state and endogenous protective pathways during pregnancy [5].…”
Section: Introductionmentioning
confidence: 99%
“…To date, four mammalian HtrAs (HtrA1-4) have been identified [1][2][3][4][5][6][7] , and their dysregulation is associated with a number of diseases, including cancer, arthritis, neurodegenerative disorders, age-related macular degeneration, and pregnancy diseases [8][9][10][11][12][13][14][15][16][17] . In particular, HtrA1 and HtrA3 have been suggested as tumor suppressors, because they are down-regulated in a number of cancers and this reduction is suggested to promote tumorigenesis [18][19][20][21][22] .…”
mentioning
confidence: 99%